Exploring ‘place-based’ initiatives in philanthropic community develop ment: A transnational examination of Canadian and US Foundations - Newton, Josh; Rabinowitz Bussell, Mirle; Martinez-Cosio, Maria; Pole, Nancy; Fontan, Jean-Marc (Local Development & Society, 2024)
Though the concept of place-based philanthropy is common parlance in c ommunity development scholarship and practice, there is still uncertai nty around its meaning due to the multidisciplinary nature of its stud y and definitional variation among and between scholars and practition ers. This article presents findings from a recently edited volume crea ted by a binational research team. Ten cases of philanthropic initiati ves were explored to develop a transnational understanding of foundati on engagement in place-based philanthropy. Place-based philanthropy wa s explored by considering collaboration with other stakeholders, initi ative evaluation, systems change efforts, and issues of power, equity, and justice. Our findings suggest that place-based philanthropy among foundations is heterogeneous. While some foundations adhere to tradit ional forms of place-based philanthropy, others are pushing the bounda ries of this type of work. This article urges both academics and pract itioners to reimagine place-based philanthropy for transformative purp oses.
Keywords: Place-based philanthropy; community development; equity and justice; systems change; transnational study